Growth and electrical characterization of thin ﬁlm silicon on MG-Si for solar cell applications - Davíð Már Daníelsson 1979- (2009)
Thin ﬁlms of silicon for solar cell applications were grown by liquid phase epitaxy (LPE). The ﬁlms were grown on semi-insulating single-crystalline silicon, p-type single-crystalline silicon and metallurgical grade silicon (MG-Si). MG-Si substrates have higher impurity concentrations than traditional electronic grade silicon and are used as low-cost alternatives to single crystalline substrates. p-n junctions were prepared by growing n-type silicon on p-type MG-Si substrates. The as-grown samples were hydrogenated to improve their electrical quality. Electrical characterization along with a morphology study was made on the grown samples. It was demonstrated that it is possible to produce a low-cost solar cell using metallurgical grade silicon substrates. However, hydrogenation is essential to achieve the desired electrical properties. This work was partially supported by the Icelandic Research Fund and the Energy Research Fund of the National Power Company of Iceland